Sustained blood pressure reduction with chronic 1,2,3,4- tetrahydroisoquinolines administration in young adult, spontaneously hypertensive rats - Abdullah, Aszrin; Mohd. Shah, Azarisman; Abdul Razak, Tariq; Mohd Noor, Noriah (2011)
Background: Adrenaline plays a role in the pathogenesis of essential hypertension through excessive stimulation of the adrenomedullary hormonal system. Pharmacological inhibition of the adrenomedullary hormonal system should result in chronic, sustained blood pressure (BP) reduction. Objective: To study the effect of adrenaline synthesis enzyme (phenylethanolamine N-methyltransferase (PNMT)) inhibitor on blood pressure of young adult spontaneously hypertensive rats (SHRs), by utilising 1,2,3,4-tetrahydroisoquinolines (THIQ). Methods: 14 young adult male and female SHRs weighing between 160 and 270g were studied. 8 study rats administered intraperitoneally with daily THIQ (Treated) and 6 age-matched controls (Control) were included. Indirect systolic blood pressure (SBP) was measured by tail cuff method prior to drug study (baseline), 2-hours post-administration on D1, D7 and D14. Results: The mean baseline SBP in Treated and Control SHRs were 172.79 + 15.61 vs 171.69 + 17.27 mmHg respectively (p=1.00). The mean SBP at D1 were 143.00 + 32.43 vs 171.69 + 17.27 mmHg respectively (p=0.02). The mean SBP at D7 were 131.83 + 28.42 vs 173.06 + 19.62 mmHg respectively (p=0.03). The mean SBP at D14 were 152.42 + 24.96 vs 180.08 + 14.59 mmHg respectively (p=0.04). There were no significant differences in plasma catecholamine levels of control SHR group observed after 2-weeks. All treated SHR plasma catecholamine levels dropped 2-weeks following the PNMTI administration. However, the differences in catecholamine levels before and after treatment were only statistically significant in the group’s plasma adrenaline levels (p= 0.04). Comparison between groups showed the treated group’s plasma adrenaline and NA show a reduced trend following treatment with PNMTI but the differences were not statistically significant. Plasma dopamine levels of the group treated with PNMTI were significantly different (p= 0.01) compared to the control group. There was no significant difference in the mean weight of the two groups throughout the study duration. Conclusion: Chronic 1,2,3,4-tetrahydroisoquinolines administration is an effective inhibitor of PNMT, the enzyme that catalyzes the terminal step in adrenaline biosynthesis, thereby resulting in susta